Subjectivity and Reflection in Marin Heidegger’s Early Freiburg Lectures - Suárez Tomé, Danila (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
In this paper we aim to draw the distinction between the preteoretical subjectivity and the knowing subject in the early Freiburg lectures by Martin Heidegger from the perspective of the methodological function and the ontological character of the reflection, in order to think whether one can speak of a notion of non-egological subjectivity in the Heideggerian approach. We understand by «non-egological subjectivity», the original subjective domain of human existence, prior to the constitution of the ego. For our purpose we address, in a first instance, the notions of original discourse and derived discourse. In a second moment, we aim to distinguish the pretheoretical subjectivity from the original subjectivity in order to analyze if it is possible to talk about the presence of a non-egological subjectivity in Heidegger.
Keywords: reflection; subjectivity; self